2017
DOI: 10.1016/j.egja.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

GlideScope versus McCoy laryngoscope: Intubation profile for cervically unstable patients in critical care setting

Abstract: Background: Endotracheal intubation for cervically unstable patients remains a challenging procedure. We compared the utility of a relatively new promising airway tool ''GlideScope" (GL) with the routinely used McCoy laryngoscope in our critical care unit. Methods: Forty intubated patients with suspected or proved cervical spine injury who were scheduled for replacing a conventional endotracheal tube (ETT) by ETT with subglottic suction facility were enrolled in this randomized controlled trial. Patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…256,266 Randomized controlled trials reported equivocal findings for laryngoscopic view, intubation success, first attempt intubation success, and time to intubation when hyperangulated videolaryngoscopes were compared with nonangulated videolaryngoscopes for anticipated difficult airways (Category A2-E evidence). 257,259 Observational studies indicated intubation success rates for videolaryngoscopes ranging from 85 to 100% of patients [267][268][269][270][271][272][273][274][275] and first attempt successful intubation rates ranging from 51 to 100% 267,269,[271][272][273][274][275] (Category B3-B evidence). Case reports observed videolaryngoscope intubation successes with a wide range of difficult airway conditions (Category B4-B evidence).…”
Section: Anticipated Difficult Airway Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…256,266 Randomized controlled trials reported equivocal findings for laryngoscopic view, intubation success, first attempt intubation success, and time to intubation when hyperangulated videolaryngoscopes were compared with nonangulated videolaryngoscopes for anticipated difficult airways (Category A2-E evidence). 257,259 Observational studies indicated intubation success rates for videolaryngoscopes ranging from 85 to 100% of patients [267][268][269][270][271][272][273][274][275] and first attempt successful intubation rates ranging from 51 to 100% 267,269,[271][272][273][274][275] (Category B3-B evidence). Case reports observed videolaryngoscope intubation successes with a wide range of difficult airway conditions (Category B4-B evidence).…”
Section: Anticipated Difficult Airway Managementmentioning
confidence: 99%
“…Observational studies indicated intubation success rates for videolaryngoscopes ranging from 85 to 100% of patients 267–275 and first attempt successful intubation rates ranging from 51 to 100% 267,269,271–275 (Category B3-B evidence ). Case reports observed videolaryngoscope intubation successes with a wide range of difficult airway conditions (Category B4-B evidence ).…”
Section: Anticipated Difficult Airway Managementmentioning
confidence: 99%